Local Government Commitment to the Smoke-Free Policy in Indonesia - Rahmayanti, K P (KnE Life Sciences, 2019)
A growing number of local governments have already enacted a smoke-free policy in Indonesia. This promising phenomenon indicates the commitment of local governments to overcoming the high smoking prevalence through smoke-free policies. This study aims to describe the enactment and implementation of the smoke-free policy in Indonesia. The cross-sectional study employs descriptive research to observe and investigate the enactment and implementation of the smoke-free policy in all local government levels in Indonesia up to December 2016 and on secondary data from previous research. The results of the study find that the implementation of the smoke-free policy requires strong commitment from the local government leader. There are variations in degree of smoke-free implementation at the local level, so this breakthrough cannot decrease smoking prevalence without budget allocation support and tobacco control activities, especially for promotion and prevention steps. All of these driving forces rely on local government’s commitment to control tobacco consumption through the smoke-free policy. The policy also needs politically driven forces, from leaders to street-level bureaucrats. These findings increase our knowledge of the progress of smoke-free policies in Indonesia and are useful guidance for academics or government officials to conduct further study or follow-up enforcement of the implementation of the smoke-free policy. Keywords: Smoke-Free Policy, Local Government, Commitment